Appraisals of disability and psychological adjustment in veterans with spinal cord injuries. (2nd November 2021) - Russell, Matthew; Ames, Herb; Dunn, Callie; Beckwith, Sarah; Holmes, Sally A.
Abstract : Context/Objective: Following a spinal cord injury or disability (SCI/D), cognitive appraisals are a marker of psychological adjustment. The present study evaluated the clinical utility and discriminant validity of the Appraisals of DisAbility Primary and Secondary Scale – Short Form (ADAPSS-sf). The ADAPSS-sf was evaluated on 1. identification of individuals experiencing poor psychological adjustment and 2. prediction of life satisfaction beyond measures of emotional distress. Design: A retrospective study was completed using ROC analyses and odds ratios to identify the clinical utility of the ADAPSS-sf. In addition, blocked hierarchical regression explored the ADAPSS-sf predictive characteristics for satisfaction with life beyond measures of emotional distress. Setting: Veteran's Health Administration SCI Center. Participants: Ninety outpatient veterans with SCI/Ds. Outcome Measures: Measures of psychological adjustment post-SCI/D included the PHQ-9, GAD-7, PC-PTSD, and the Diener Satisfaction with Life Scale (SWLS). The ADAPSS-sf was used as a measure of cognitive appraisals. Results: Results indicated the ADAPSS-sf is effective in identification of poor psychological adjustment, P < .001. Diagnostic odds ratios and ADAPSS-sf cut scores were selected to prioritize sensitivity (7.17,  ≤ 11), specificity (68.25,  ≥ 22), or a balance of the two (16.32,  ≤ 19). Hierarchical regression indicated the ADAPSS-sf accounted for unique variance in life satisfaction beyond measures of emotional distress, (Δ R 2  = .20, β  = −.66, t (89) = 6.54, P < .001). Conclusion: Results indicated SCI/D specific appraisals are predictive of concurrent poor psychological adjustment and provide insight into satisfaction with life beyond measures of emotional distress.